Biochemical Characterization of the DASH‐Type Cryptochrome CryD From Fusarium fujikuroi. (11th September 2015) - Castrillo, Marta; Bernhardt, Adrian; Ávalos, Javier; Batschauer, Alfred; Pokorny, Richard
Abstract: Proteins from the cryptochrome/photolyase family utilize UV‐A, blue or even red light to achieve such diverse functions as repair of DNA lesions by photolyases and signaling by cryptochromes. DASH‐type cryptochromes retained the ability to repair cyclobutane pyrimidine dimers (CPDs) in single‐stranded DNA regions in vitro . However, most organisms possess conventional CPD photolyases responsible for repair of these lesions in vivo . Recent work showed that the DASH‐type cryptochrome CryD plays a regulatory role in diverse light‐dependent processes in Fusarium fujikuroi . Here, we report our in vitro studies on heterologously expressed Ff CryD. The purified protein contains N 5, N 10 ‐methenyltetrahydrofolate and flavin adenine dinucleotide as cofactors. Photoreduction and DNA photorepair experiments confirmed that Ff CryD is active in light‐driven electron transfer processes. However, the protein showed comparable affinities for CPD‐comprising and undamaged DNA probes. Surprisingly, after purification, full‐length Ff CryD as well as a truncated version containing only the PHR domain bound RNA which influenced their behavior in vitro . Moreover, binding of Ff CryD to RNA indicates a putative role in RNA metabolism or in posttranscriptional control of gene expression. Abstract : The study biochemically characterizes the heterologously expressed and purified DASH‐type cryptochrome CryD that plays regulatory roles in Fusarium fujikuroi . As an example, CryD inhibits the light‐induced accumulation of a red polyketide pigment bikaverin in F. fujikuroi mycelia. Colonies of F. fujikuroi wild‐type strain (Wild type) and of a representative CryD null‐mutant strain (Δ cryD ) grown for 7 days at 30°C on a minimal medium with low nitrogen content in white light (Light) are colored differently whereas colonies of the two strains grown in darkness (Dark) show the same color.